Meta-survey on medium access control surveys in wireless sensor networks. (August 2016) - Arain, Waseem M; Ghani, Sayeed
Medium access control layer has been the hotbed of research in the field of wireless sensor networks since huge amount of research in wireless sensor networks has focused on saving energy and lately reducing latency. For the most part, medium access control layer solutions in wireless sensor networks are entrusted to save energy, to reduce latency, and at times to ensure reliability perhaps through cross-layer solutions. In this article, we review the surveys at medium access control layer and point to readers some of their strengths and relevancies to medium access control layer protocols. Furthermore, we classify the surveys subject-wise to show trend and usability. To cross compare, we devise a unified lexicon for the purpose and expose the coverage given to the wireless sensor networks' medium access control protocols by different studies. We present medium access control solutions' popularity on a known but hitherto unused metric: average citations/year from over 200 medium access control solutions. Our approach to assess the impact factor of protocols for ranking is validated prima facie from the coverage of these solutions by top ranking surveys. We believe it is the widest of such a study involving more than 30 survey papers and over 200 wireless sensor network medium access control protocols.